Assessment of the Relationship between Ki-67 Expression and Different Clinicopathological Factors of Adenoid Cystic Carcinoma: A Retrospective Immunohistochemical Study - Mohammed Al Zubidi; Mustafa Mohammed Abdulhussain; Ali Sami Mohsin (International Journal of Biomedicine)
Background: Adenoid cystic carcinoma (ACC) is an aggressive cancer that can affect many glands in the body, including the salivary glands, lacrimal glands, and upper digestive tract. Although slow growing, ACC has a poor prognosis due to its local invasion as well as elevated recurrence rates. Ki-67 is a widely utilized nuclear indicator, a type of protein found in nature, including cell proliferative immunomarkers. The exact role of Ki-67 remains unclear despite its importance as a predictive and prognostic biomarker. The present study aimed to assess the significance of Ki-67 expression in ACC lesions and their correlation with clinicopathological characteristics. Methods and Results: Thirty-three histopathology-confirmed ACC cases were included in this study. The expression of Ki67 was evaluated by immunohistochemistry. The immunohistochemical staining revealed brown nuclear positivity of Ki-67 in 33 study samples. Of these, 15(45.5%) had a weak score (+1), 13(39.4%) - a moderate score (+2), and 5(15.2%) - a high score (+3). The distribution of Ki-67 expression according to the grading of ACC lesions was weak and moderately positive for low-grading cases, low positive for moderate-grading cases, and moderately positive for severe-grading cases, with no significant correlation. Regarding the tumor site, the peak incidence for weak, moderate, and high positive staining of Ki-67 expression was at the palate site, followed by the parotid gland and orbit sites, and then the others. Conclusion: There is a statistical association between Ki-67 level and tumor location parameters. The elevated Ki-67 labeling value relates to poor prognosis.